Diversity in the workforce - DiTomaso, Nancy; Post, Corinne (Amsterdam ; Oxford : Elsevier JAI, 2004)
Increasing diversity in the workforce has several sources: (a) the changing demographic structure of the U.S., (b) the increased importance of globalization to profits and long term survival in many companies, and (c) changes in the structure of how work gets done. People bring with them into organizations the patterns of behavior and thinking, the networks, the social pressures, the habits, and strategies of action that they learned before joining the organization. Further, people are shaped by the perceptions, attitudes, and behaviors of others in regard to them. Although many organizations in the past have tried to homogenize behavior and attitudes by developing their own organizational cultures, the reality in most organizations is the existence of distinct subcultures and microcultures, as each group tries to find its own place, often in competition with others. This volume of the Sociology of Work addresses a number of issues that are brought to the fore because of diversity in the workforce: the structure, impact, and mechanisms of social networks; the policies and political dynamics around trying to redistribute benefits among social groups; issues regarding work and family, especially for professional workers in male dominated jobs; and the link between diversity in the workforce and broader issues of inequality. This set of papers address many of the emerging empirical and theoretical work in the study of diversity in the workforce and create an agenda for future work in the area.
Workforce diversity: why, when, and how / Corinne Post and Nancy DiTomaso -- Who benefits? gender differences in returns to social network diversity / Lisa Torres and Matt L. Huffman -- Networks of inclusion and exclusion in the economic concentrations of Asia Indian immigrants in New York and London / Maritsa V. Poros -- If I know it, will I share it?: the potential effects of group composition on the creation and stability of organizational knowledge / Melvin L. Smith -- The impact of social capital on African-American and women survivors of organizational downsizing / Rochelle Parks-Yancy -- Predicting affirmative action attitudes: interactions of the effects of individual differences with the strength of the affirmative action plan / David A. Kravitz and Stephen L. Klineberg -- Between solidarity and individualism: collective efforts for social reform in the heterogenous workplace / Orly Lobel -- Hierarchy-enhancing versus hierarchy-leveling perspectives in organizations: valuing value diversity in the new economy / Wayne Eastman -- Women, men, career and family in the U.S. young physician labor force / Susan W. Hinze -- Motherhood and career commitment to the legal profession / Jean E. Wallace -- The marriage advantage for men in science and engineering organizations / Corinne Post, George F. Farris and Rene Cordero -- Understanding the effects of workforce diversity on employment outcomes: a multidisciplinary and comprehensive framework / Sheryl Skaggs and Nancy DiTomaso.
Includes bibliographical references.
Description based on print version record.
Keywords: Diversity in the workplace -- Sociological aspects; Multiculturalism; Intercultural communication; Sociology: work & labour; Social Science -- Sociology -- General